Differential responses of soil bacteria and fungi to altered precipitation in a meadow steppe - Yang, Xuechen; Zhu, Kai; Loik, Michael E.; Sun, Wei (Geoderma, 2021)
•Precipitation induced the changes in bacterial diversity and structure.•Fungal community was sensitive to inter-annual differences in precipitation.•Higher annual precipitation shifted the dominance of microbe from bacteria to fungi.•Microbial richness in response to precipitation was linked to multiple soil factors. Soil microorganisms are essential participants in ecosystem processes, yet their composition, diversity, and function are affected by altered precipitation. The patterns and key processes driving the effects of changes in precipitation on soil bacterial and fungal communities remain unclear. To better understand how changes in precipitation may affect soil microorganisms, we conducted a three-year field precipitation manipulation experiment, with treatments ranging from 50% reduction to 50% increases in precipitation, in a meadow steppe located in northeast China. Our results demonstrated that the bacterial community was more sensitive to changes in precipitation than the fungal community. The fungal community was sensitive to inter-annual differences in precipitation, but not to the treatment-induced changes in precipitation. Increased annual precipitation shifted the dominance of the microbial community from bacteria to fungi. Over the precipitation range (200–280 mm) soil microbial biomass and diversity are maximal, below the long-term mean annual precipitation (430 mm) for this site. Soil water content, pH, and total phosphorus were the main factors related to the variance in soil microbial community diversity. Results show non-linear, time-dependent, and interacting responses of bacterial and fungal biomass and diversity to soil properties under gradients of altered precipitation magnitude in this semi-arid grassland.